2020
DOI: 10.1177/0886260520951309
|View full text |Cite
|
Sign up to set email alerts
|

Betrayal Trauma and Gender: An Examination of the Victim–Offender Overlap

Abstract: Empirical research has demonstrated widespread support for the association between violent victimization and offending, or the “victim–offender overlap.” This study adds to this body of research by applying the betrayal trauma framework to investigate whether the relationship between the victim and perpetrator impacts the presence of the victim–offender overlap and whether these effects differ across gender. Specifically, this study utilizes a series of binary logistic regressions to investigate (a) whether vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Findings regarding gender have been mixed. Gender has not distinguished the V-O overlap in some studies (Muftić et al, 2015; Reingle, Jennings, & Maldonado-Molina, 2012; Tillyer & Wright, 2014), but was a significant characteristic in two nationally representative studies (Kushner, 2020; Taylor et al, 2019). Background factors such as substance use have also been implicated in the V-O overlap (Klevens et al, 2002; Reingle, Staras, et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Findings regarding gender have been mixed. Gender has not distinguished the V-O overlap in some studies (Muftić et al, 2015; Reingle, Jennings, & Maldonado-Molina, 2012; Tillyer & Wright, 2014), but was a significant characteristic in two nationally representative studies (Kushner, 2020; Taylor et al, 2019). Background factors such as substance use have also been implicated in the V-O overlap (Klevens et al, 2002; Reingle, Staras, et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…This has included discussion of whether witnessing intimate partner violence is a risk factor for CPV, and the nature of any causal pathways. Evidence suggests that children who experience family violence are at heightened risk of violent behaviour generally (Kushner 2020), and that between 50 -80% of children engaged in CPV have witnessed or been subjected to violence at home, although the causal mechanisms between violent victimization and CPV remain unclear (Simmons et al 2018: 38-9). The complex interplay between intimate partner violence and CPV is a central theme of this article.…”
Section: Introductionmentioning
confidence: 99%
“…An additional dimension of ADA requiring more empirical work concerns gender differences [12,13]. Although research has identified the co-occurring nature of victimization and perpetration across genders [2,6,14], several studies found gender differences in ADA experiences [7,15,16]. For example, some research finds that boys and men are more likely to perpetrate ADA than girls and women, who are more likely to experience victimization [4].…”
mentioning
confidence: 99%